1994
DOI: 10.1128/jb.176.5.1282-1286.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cytosylglucuronic acid synthase (cytosine: UDP-glucuronosyltransferase) from Streptomyces griseochromogenes, the first prokaryotic UDP-glucuronosyltransferase

Abstract: Cytosylglucuronic acid synthase (cytosine: UDP-glucuronosyltransferase), the first prokaryotic UDP-GT and a key enzyme in the biosynthesis of the antibiotic blasticidin S, was purified 870-fold. It has optimum activity at a pH of 8.4 to 8.6, Kms of 6.0 (UDP-glucuronic acid) and 243 (cytosine) microM, and a maximum rate of metabolism of 14.6 mumol/min/mg. The apparent M(r) is 43,000. Activity was slightly enhanced by Mg2+ or Ca2+ but was not inhibited by EDTA. Activity was strongly inhibited by UDP. Cytosylgluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In addition to the structural resemblance of MIL and blasticidin S (Scheme ), fermentation and biochemical studies also support related biosynthetic pathways. Similar to the findings with MIL, yields of blasticidin S increased nearly two‐fold when free cytosine was added to cultures of the producing organism 20. More recently, BlsM was characterized from the blasticidin S biosynthetic pathway as a CMP hydrolase, and was shown to be responsible for generating free cytosine from CMP,21 analogous to the conversion of HMCMP to HMC.…”
Section: Introductionsupporting
confidence: 67%
“…In addition to the structural resemblance of MIL and blasticidin S (Scheme ), fermentation and biochemical studies also support related biosynthetic pathways. Similar to the findings with MIL, yields of blasticidin S increased nearly two‐fold when free cytosine was added to cultures of the producing organism 20. More recently, BlsM was characterized from the blasticidin S biosynthetic pathway as a CMP hydrolase, and was shown to be responsible for generating free cytosine from CMP,21 analogous to the conversion of HMCMP to HMC.…”
Section: Introductionsupporting
confidence: 67%
“…Interestingly, although glucuronosyltransferases are commonly observed in mammalian metabolism, [21,22] few have been described in prokaryotic organisms. [23,24] To our knowledge, this is the first isolation of glucuronidated tetracycline biosynthetic intermediates, although glucosylated, truncated tetracycline intermediates have been reported to be produced by a S. rimosus mutant. [25] In summary, by using gene disruption and heterologous reconstitution experiments, we have characterized the function of OxyE as a C-4 monooxygenase during oxytetracycline biosynthesis in S. rimosus.…”
Section: Discussionmentioning
confidence: 93%
“…[10] Gould and co-workers were able to show that addition of exogenous cytosine to S. griseochromogenes culture media increased BS production by 1.6-fold and elevated the production of the intermediate cytosylglucuronic acid (CGA) by up to 70-fold. [11] These results were not surprising as intracellular concentrations of cytosine are likely quite low inasmuch as free cytosine is not an intermediate in pyrimidine biosynthesis. [12] The stimulation of BS production upon cytosine supplementation suggested that the availability of free cytosine might be a limiting factor in blasticidin biosynthesis.…”
Section: Introductionmentioning
confidence: 91%